2022
DOI: 10.1242/dmm.049538
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two cancer stem cell-like populations in triple-negative breast cancer xenografts

Abstract: Gene expression analysis at the single-cell level by next generation sequencing has revealed the existence of clonal dissemination and microheterogeneity in cancer metastasis. The current spatial analysis technologies can elucidate the heterogeneity of cell–cell interactions in situ. To reveal the regional and expressional heterogeneity in primary tumors and metastases, we performed transcriptomic analysis of microtissues dissected from a triple-negative breast cancer (TNBC) cell line MDA-MB-231 xenograft mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Figures 10C and 10D display representative images of metastatic tumors in the liver. The MDA-MB-231 tumor used in the xenograft model is well-known to metastasize to various organs, including the liver, lymph nodes, lungs, bones, and brain [36]. Although the nanoparticle formulation inhibited cell migration in vitro, a similar effect was not observed in vivo at the current dose.…”
Section: Discussionmentioning
confidence: 86%
“…Figures 10C and 10D display representative images of metastatic tumors in the liver. The MDA-MB-231 tumor used in the xenograft model is well-known to metastasize to various organs, including the liver, lymph nodes, lungs, bones, and brain [36]. Although the nanoparticle formulation inhibited cell migration in vitro, a similar effect was not observed in vivo at the current dose.…”
Section: Discussionmentioning
confidence: 86%
“…[ 22 , 23 ] Silencing HMGA1 can block the metastasis of breast cancer and colorectal cancer and reduce the proportion of tumor stem cells. [ 24 26 ] As reported in a recent study, the high expression of HMGA1 may be induced by the secretion of breast cancer cells, and signals may be sent through the advanced glycation end-products receptor, which would promote invasiveness. [ 26 ] In addition, previous studies demonstrated that the overexpression of HMGA1 can regulate the epigenetic silencing of genes related to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1.0 × 10 6 NMuMG‐luc‐HOXB7 cells, NMuMG‐luc‐HOXB7‐shGFP cells, or NMuMG‐luc‐HOXB7‐shSTAT3#3 cells were transplanted into fourth fat pads of 6‐weeks‐old BALB/cSlc‐nu/nu female mice as previously described (Nakayama et al, 2017, 2022). After the injection, the transplantation sites were palpated for every 2–3 days to measure tumor formation time and mice were monitored primary tumor formation and metastasis formation by in vivo imaging system (IVIS Lumina Xr3; Perkin‐Elmer, Waltham, MA) for every week.…”
Section: Methodsmentioning
confidence: 99%